Peran Pendamping Minum Obat (PMO) dalam Keteraturan Konsumsi Obat Klien TBC - Wartonah Wartonah; Eska Riyanti; Nelly Yardes (Jurnal Keperawatan, 2019)
Tuberculosis is a contagious pulmonary infection and the biggest cause of death after cardiovascular disease and diabetes mellitus. The non-compliance of patients with pulmonary TB in taking medication causes the patient's recovery rate to be low, high mortality rates and recurrence increases and has an impact on bacterial resistance to some anti-tuberculosis drugs and is very difficult to cure. This study aims to determine the factors most associated with adherence to taking anti-pulmonary TB drugs in the Cipayung District Health Center East Jakarta area. The research method used is Cross sectional. The sample used was 60 respondents who matched the inclusion criteria. Data collection was done using questionnaires and data analysis using Chi-Square test. Data analysis showed that there was a significantly relationship between role of PMO with OR 2,6 (p value = 0,000) with adherenceto taking anti-pulmonary TB drugs. The results showed that TB clients 2.6 times would regularly take TB medication if the PMO reminded them of taking medication